Correlation of Dance Functional Status with Lower Limb Flexibility, Power and Dynamic Balance in Recreational Ballet Dancers – A Cross-Sectional Study - Priyanka Kumbhar; Neetu Mahapatra (Baltic Journal of Sport and Health Sciences)
Background: Paediatric ballet dancers are particularly prone to injuries due to the demanding nature of their art form, exacerbated by intensive training during crucial growth and maturation phases. The prevalence of injuries, especially those aﬀecting lower limbs, hampers dancers’ functional capacity. Unlike their professional counterparts, recreational ballet dancers lack specialized training, heightening their vulnerability. The accumulation of repetitive injuries often hampers their ability to attain the highest levels of achievement in their careers, underscoring the necessity to identify and comprehend contributing factors. The aim is to fnd a correlation between the Dance Functional Outcome Survey (DFOS) and critical factors like lower limb ﬂexibility, power, and dynamic balance among recreational ballet dancers.